Clear and simple - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
Throughout West Africa, ginger is used as a beverage. In Côte d Ivoire for instance, fresh ginger is locally used to make a refreshing drink: gnamakudji. The roots are peeled, crushed, soaked with water and sweetened with sugar. The disadvantage...